Characteristics of a Successful Exchange Rate System - Masson, Paul (Occasional Papers; Occasional Paper ;, 1991)
This study identifies the key characteristics of a successful exchange rate system. It focuses on regimes in the industrial countries and consider the implications for the operation of the international monetary system.